A modified discrete filled function algorithm for solving nonlinear discrete optimization problems - Woon, S.; Rehbock, Volker; Loxton, Ryan (COC Publications, Curtin University, 2012)
The discrete filled function method is a global optimization tool for searching for the best solution amongst multiple local optima. This method has proven useful for solving large-scale discrete optimization problems. In this paper, we consider a standard discrete filled function algorithm in the literature and then propose a modification to increase its efficiency.